Apigenin upregulation of CD26/DPPIV on colon epithelial cells requires inhibition of casein kinase 2. Issue 10 (20th August 2020) - Lefort, Émilie C.; Diaconu, Bogdan; Bentley, Victoria L.; Blay, Jonathan
Abstract: CD26/DPPIV is a cell surface glycoprotein found on cells of the intestinal epithelium including those of the colon. We have previously shown that the dietary flavone apigenin (4′, 5, 7‐trihydroxyflavone) upregulates CD26/DPPIV on colon cells. Flavonoids such as apigenin interfere with the action of multiple cellular protein kinases and have the capacity to modulate the cell exterior and its ability to interface with the local environment through different signaling pathways. We show here that the ability of apigenin to upregulate CD26/DPPIV is exerted through and requires the activity of casein kinase 2 (CK2). Inhibitors of CK2 that are distinct from apigenin (emodin, 6‐methyl‐1, 3, 8‐trihydroxyanthraquinone; TBB, 4, 5, 6, 7‐tetrabromobenzotriazole; and DRB, 5, 6‐dichlorobenzimidazole 1‐β‐D‐ribofuranoside) showed a dose‐dependent ability to increase CD26/DPPIV and had the same maximal effect when combined with apigenin at submaximal concentrations. Knockdown of CK2 with siRNA abrogated the ability of apigenin to upregulate CD26/DPPIV. Apigenin treatment of cells had no effect on the levels of CK2 protein, consistent with an inhibition of activity of the enzyme. Apigenin's upregulation of CD26/DPPIV in differentiated human colon epithelial cells depends upon inhibition of CK2 activity. This is a key step in enabling apigenin's ability to regulate the functions of intestinal epithelial cells. Abstract : The dietary flavone apigenin (4′, 5, 7‐trihydroxyflavone) upregulates CD26/DPPIV on intestinal epithelial cells. CD26/DPPIV is a cell surface protein that cleaves N‐terminal dipeptides from several key cellular regulators and modulates their activity. A key early step in this action of apigenin is to inhibit the activity of the enzyme casein kinase 2 (CK2). This is a necessary part of apigenin's ability to regulate the multiple functions of CD26/DPPIV on intestinal epithelial cells.